2018
DOI: 10.2478/eje-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Human Disturbance is the Major Determinant of the Habitat and Prey Preference of the Bengal Tiger (Panthera tigris tigris) in the Chitwan National Park, Nepal

Abstract: We studied the impact of human disturbances on the habitat and prey preference of tiger by walking along transects in different sites of the Chitwan National Park, Nepal. The study found that tiger mostly preferred successional forests, grasslands and floodplains while avoiding the Shorea forests. Tiger strongly preferred prey abundant areas and strongly avoided the human disturbed areas. The prey preference of tiger obtained through scat analysis showed the highest preference of medium sized prey and less pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Regular disturbances caused by human activities could offer a change in distribution and behaviour of mammal that consequently increases conflict with people (Cheyne et al 2016, Adhikari et al 2018. Hence, the habitat and prey preference of carnivores also depends on the degree of habitat disturbances in the human dominated landscapes (Bhattarai & Kindlmann 2018). In general terms, diversity, abundance, total biomass, and mean biomass of species tend to decrease with increasing human disturbance (Oberosler et al 2017).…”
Section: Effects Of Topography On Distribution Of Mammalsmentioning
confidence: 99%
“…Regular disturbances caused by human activities could offer a change in distribution and behaviour of mammal that consequently increases conflict with people (Cheyne et al 2016, Adhikari et al 2018. Hence, the habitat and prey preference of carnivores also depends on the degree of habitat disturbances in the human dominated landscapes (Bhattarai & Kindlmann 2018). In general terms, diversity, abundance, total biomass, and mean biomass of species tend to decrease with increasing human disturbance (Oberosler et al 2017).…”
Section: Effects Of Topography On Distribution Of Mammalsmentioning
confidence: 99%
“…Sheep and buffalo rearing are common practices, and the reports of the livestock picking is comparatively less than from other landscapes (Singh et al 2013;Athreya et al 2015;Gubbi et al 2020;Puri et al 2020). When plenty of resources are available in the forest, the big cats, especially tiger, never venture in human habituations (Karanth et al 2004;Wang and Macdonald 2009;Odden et al 2010;Bhattarai and Kindlmann 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its larger body size than the leopard, the tiger includes prey of a higher weight class in its diet, allowing it to maintain a stable large prey population (Seidensticker 1976;Karanth et al 2004). Tigers prefer relatively large and uninterrupted ranges with plenty of prey and avoid human settlements (Karanth et al 2004;Wang and Macdonald 2009;Odden et al 2010;Bhattarai and Kindlmann 2018). They prefer open grasslands, logged areas, and bordered areas as their primary habitats, whereas leopards are highly malleable and rely on human-modified landscapes such as croplands, tea estates, and agricultural plantations for movement, and the tiger avoidance varies depending on prey density (Johnsingh 1983;Bailey 1993;Linkie et al 2003;Odden et al 2010;Athreya et al 2013;Bhattacharjee and Parthasarathy 2013;Navya et al 2014;Odden et al 2014;Sidhu et al 2015;Kshettry et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Janssen et al (2016) found that the enamel of a Trinil tiger specimen has carbon- and oxygen-isotopic values “reflecting a food chain with a mixed C 3 /C 4 base.” The Trinil taxon is one of numerous subspecies of Panthera tigris . Of the South Asian tiger, Bhattarai (2011: 1) summarized, “the basic habitat requirements … include the thick cover of forest, proximity to water and … an abundance of large and medium-sized prey” (also, Chanchani et al 2014). Tigers still inhabit Sumatra, where they prefer thick understory, and prey, by surprise and stealth, on medium- to large-ungulates and ground-dwelling primates, such pigs, muntjacs, deer and macaques (e.g., Goodrich et al 2015, Linkie et al 2008, Wibisono et al 2011).…”
Section: Endnotesmentioning
confidence: 99%